A Conrad Chronology - Knowles, O.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Newly revised and enlarged, the second edition of A Conrad Chronology draws upon a rich range of published and unpublished materials. It offers a detailed factual record of Joseph Conrad's unfolding life as seaman and writer as well as tracing the compositional and publication history of his major works.
Keywords: Literature, Modern—20th century; British literature; Fiction; Literature—Philosophy.; Twentieth-Century Literature; British and Irish Literature; Fiction; Literary Theory